A simplified approach of numerical seismic model updating for deep braced excavation using centrifuge test - Md Mehidi Hassan; Dong Van Nguyen; Yun Wook Choo; Dookie Kim (Results in Engineering, 2024)
The numerical modeling and centrifuge test are very effective tools in demonstrating the actual behavior of deep excavation, but the preciseness in verification is crucial. This study proposes a Response Surface (RS) based technique for updating a deep-braced excavation seismic numerical model based on a small-scale centrifuge test. The proposed method involves establishing a relationship between soil properties and seismic characteristics of the system and creating an RS model to predict both. The RS model is made via a series of Eigenvalue analyses using the Design of Experiments (DOE) approach. The constructed RS model shows excellent goodness of fit. The seismic characteristics of the model in the centrifuge test are estimated using the Frequency Domain Decomposition (FDD) approach. By setting that test result as a target in the RS model, soil properties are updated through back analysis, and minimum error with the numerical response is achieved. The established RS model predicts seismic characteristics with less than a 1.5 % difference with numerical responses. Thus, an efficient three-dimensional (3D) numerical model on a prototype scale is made. The efficiency of the seismic response of the updated model is checked by acceleration time history analysis, and it shows trends similar to those of the centrifuge test.